2015
DOI: 10.3389/fncel.2015.00462
|View full text |Cite
|
Sign up to set email alerts
|

Type I Vs. Type II Cytokine Levels as a Function of SOD1 G93A Mouse Amyotrophic Lateral Sclerosis Disease Progression

Abstract: Amyotrophic Lateral Sclerosis (ALS) is a fatal motoneuron disease that is characterized by the degradation of neurons throughout the central nervous system. Inflammation have been cited a key contributor to ALS neurodegeneration, but the timeline of cytokine upregulation remains unresolved. The goal of this study was to temporally examine the correlation between the varying levels of pro-inflammatory type I cytokines (IL-1β, IL-1α, IL-12, TNF-α, and GFAP) and anti-inflammatory type II cytokines (IL-4, IL-6, IL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 91 publications
1
25
1
Order By: Relevance
“…The physically long motoneurons have already been shown to be vulnerable to instability in both physiological and pathological ALS animal models, including the presence of destabilizing somatic dynamics ( 27 ), axonal transport deregulation ( 28 ), metabolic insufficiency ( 29 ), inadequate calcium buffering ( 29 ), compensatory oxidative stress responses ( 29 ), and dynamic imbalances of pro- and anti-inflammatory cytokines ( 30 ). Mathematical oscillations and corresponding instabilities have also been identified in theoretical ALS models ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…The physically long motoneurons have already been shown to be vulnerable to instability in both physiological and pathological ALS animal models, including the presence of destabilizing somatic dynamics ( 27 ), axonal transport deregulation ( 28 ), metabolic insufficiency ( 29 ), inadequate calcium buffering ( 29 ), compensatory oxidative stress responses ( 29 ), and dynamic imbalances of pro- and anti-inflammatory cytokines ( 30 ). Mathematical oscillations and corresponding instabilities have also been identified in theoretical ALS models ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a considerable number of case reports and pilot studies have indicated the beneficial effects of tocilizumab on other autoimmune and chronic inflammatory diseases [ 12 ]. Interestingly, as summarized in a recent meta-analysis [ 13 ], several studies indicated that IL-6 is elevated in the spinal cord of the mouse ALS model [ 14 , 15 ]. In addition, a previous report showed that IL-6 is increased in the cerebrospinal fluid of ALS patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on these promising anti-in ammatory effects in the APP/PS1 AD mouse model, we decided to continue the treatment in another mouse model of a neurodegenerative disorder in which neuroin ammation is known as main driver of the disease. Therefore, the SOD1*G93A ALS mouse model was chosen [17,18,26,54]. SOD1*G93A mice were treated intraperitoneally for 28 days with RD2RD2 or placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In a non-pathological state, a complex signalling cascade produces a protective immune response through cytokines [22,23]. A temporal increased level of in ammatory cytokines was observed in ALS, but also in AD [24][25][26]. Like many other neurodegenerative diseases, such as AD, to date there is no curative therapy for ALS.…”
Section: Introductionmentioning
confidence: 99%